Role Playing With used Empty Packaging to Improve The Cooperation and The Learning Achievement on The Topic Additives and Addictives - Herni Budiati (Universitas Sebelas Maret, 2019)
The aims of this research is to improve the cooperation and the learning achievement on additives and addictives substances subject which is taught at grade VIIIE of SMP Negeri 22 Surakarta through the role playing with used empty packaging . The research was Classroom Action Research wich held in SMP Negeri 22 Surakarta in 2nd semester academic year 2015/2016. The research subjects were 29 students VIIIE Class of SMP Negeri 22 Surakarta. The object of the research is additives and addictives substances. Data was collected by observing learning process and doing tests of student’s achievement. The procedures in this classroom action research adopted the Kemmis and Taggart model which is conducted in 2 cycles. Each cycle consist of plan, action, observation, and reflection. Qualitative data were analyzed descriptively. The research showed an increase of cooperation and learning achievement of additives and addictives substance subject in class VIIIE SMP Negeri 22 Surakarta academic year 2015/2016 through role playing with used empty packaging